1997
DOI: 10.1029/97jb00995
|View full text |Cite
|
Sign up to set email alerts
|

Strengths of serpentinite gouges at elevated temperatures

Abstract: Abstract. Serpentinite has been proposed as a cause of both low strength and aseismic creep of fault zones. To test these hypotheses, we have measured the strength of chrysotile-, lizardite-, and antigorite-rich serpentinite gouges under hydrothermal conditions, with emphasis on chrysotile, which has thus far received little attention. At 25øC, the coefficient of friction, g, of chrysotile gouge is roughly 0.2, whereas the lizardite-and antigorite-rich gouges are at least twice as strong. The very low room tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
203
0
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 216 publications
(218 citation statements)
references
References 46 publications
13
203
0
2
Order By: Relevance
“…Again focusing on the weakest gouges, Morrow et al, (1992) found that montmorillonite was strengthened by around 50% when interlayer water was squeezed out under several hundred MPa pressure at room temperature. Moore et al (1997) found that when the serpentine variety chrysotile was sheared at increasingly higher temperatures and pressures simulating depths of up to 9 km, adsorbed water was removed and the anomalously low frictional strength increased to levels more comparable to the antigorite and lizardite serpentine varieties.…”
Section: Implications For Fault Zonesmentioning
confidence: 99%
See 1 more Smart Citation
“…Again focusing on the weakest gouges, Morrow et al, (1992) found that montmorillonite was strengthened by around 50% when interlayer water was squeezed out under several hundred MPa pressure at room temperature. Moore et al (1997) found that when the serpentine variety chrysotile was sheared at increasingly higher temperatures and pressures simulating depths of up to 9 km, adsorbed water was removed and the anomalously low frictional strength increased to levels more comparable to the antigorite and lizardite serpentine varieties.…”
Section: Implications For Fault Zonesmentioning
confidence: 99%
“…Adsorbed water, resulting from the attraction of the water dipole to electrically charged mineral surfaces, can also substantially reduce frictional strength of gouge materials by providing a low-resistance slip interface, much like the interlayer water of montmorillonite. For instance, Moore et al (1997)found that the serpentine variety chrysotile, which readily adsorbs water onto its surface, also had a coefficient of friction of 0.2 and was only half as strong as the varieties lizardite and antigorite at room temperature. Israelachvili et al (1988) separated by a thin film of water, the first few layers of water are organized at an atomic level and the shear strength is inversely related to the number of water layers present.…”
Section: Introductionmentioning
confidence: 99%
“…The influx of volatiles into mantle peridotite along faults and subsequent diffuse flow of the fluid into the rock along thermal fractures at low temperatures results in serpentinization of mantle peridotite [O'Hanley, 1996]. Both the frictional strength [Moore et al, 1997] and the fracture strength [Escartin et al, 1997a] of serpentinized mantle peridotite are less than that of unaltered peridotite. Thus, the serpentinization process probably has a substantial influence on the tectonic evolution of the oceanic lithosphere [Escartin et al, 1997b].…”
Section: Modeling Thermal Cracking In the Oceanic Lithospherementioning
confidence: 99%
“…Fluids 163 present in the mantle alter ultramafic rocks to serpentine, which can strongly influence the strength of the oceanic lithosphere [e. g., Escartin et al, 1997a;Moore et al, 1997].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, experiments on natural clay-rich fault gouges collected from the San Andreas at depths of less than 0.4 km (Morrow et al, 1982), on synthetic clay-rich fault gouges (Morrow et al, 1992) and on synthetic serpentinite gouges (Moore et al, 1997) at high temperatures and/or confining pressures and hydrostatic fluid pressures indicate coefficients of friction at in-situ conditions that are too high to be reconciled with either the heat-flow or directional constraints. In addition, both natural and synthetic fault gouges deformed in the laboratory generally fail to exhibit the slip-weakening or velocityweakening behavior required for the generation of earthquakes (e.g., Byerlee and Summers, 1976;Logan and Rauenzahn, 1987;Marone et al, 1990;Morrow et al, 1992;Reinen et al, 1994).…”
Section: Implied Fault Zone Properties and Deformation Mechanismsmentioning
confidence: 87%